Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Solve the equation for [tex]\( x \)[/tex].

[tex]\[ \frac{2}{3} x - \frac{1}{9} x + 5 = 20 \][/tex]

[tex]\[ x = \][/tex]


Sagot :

To solve the equation [tex]\(\frac{2}{3} x - \frac{1}{9} x + 5 = 20\)[/tex] for [tex]\(x\)[/tex], follow these steps:

1. Combine like terms involving [tex]\(x\)[/tex]:

The given equation is:
[tex]\[ \frac{2}{3} x - \frac{1}{9} x + 5 = 20 \][/tex]

To combine [tex]\(\frac{2}{3} x\)[/tex] and [tex]\(\frac{1}{9} x\)[/tex], first find a common denominator. The common denominator for 3 and 9 is 9. Rewrite each fraction with this common denominator:
[tex]\[ \frac{2}{3} x = \frac{6}{9} x \][/tex]
[tex]\[ \frac{6}{9} x - \frac{1}{9} x = \frac{5}{9} x \][/tex]

So the equation now is:
[tex]\[ \frac{5}{9} x + 5 = 20 \][/tex]

2. Isolate the term with [tex]\(x\)[/tex]:

Subtract 5 from both sides to isolate the term with [tex]\(x\)[/tex]:
[tex]\[ \frac{5}{9} x + 5 - 5 = 20 - 5 \][/tex]
Simplifying this gives:
[tex]\[ \frac{5}{9} x = 15 \][/tex]

3. Solve for [tex]\(x\)[/tex]:

To solve for [tex]\(x\)[/tex], multiply both sides of the equation by the reciprocal of [tex]\(\frac{5}{9}\)[/tex], which is [tex]\(\frac{9}{5}\)[/tex]:
[tex]\[ x = 15 \times \frac{9}{5} \][/tex]
Simplifying the right-hand side:
[tex]\[ x = 15 \times \frac{9}{5} = 15 \times 1.8 = 27 \][/tex]

Therefore, the solution to the equation is:
[tex]\[ x = 27 \][/tex]